2019
DOI: 10.1002/hbm.24894
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous functional architecture of the posteromedial cortex is associated with selective functional connectivity differences in Alzheimer's disease

Abstract: The posteromedial cortex (PMC) is a key region involved in the development and progression of Alzheimer's disease (AD). Previous studies have demonstrated a heterogenous functional architecture of the region that is composed of discrete functional modules reflecting a complex pattern of functional connectivity. However, little is understood about the mechanisms underpinning this complex network architecture in neurodegenerative disease, and the differential vulnerability of connectivity‐based subdivisions in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
1
6
1
Order By: Relevance
“…To the best of our knowledge, disrupted FCS within V_pcu (or any subregions of the precuneus), as a reflection of local intrinsic FC, has not been previously reported. Disrupted global FC between V_pcu and other brain regions has been consistently shown by studies investigating differential functional architecture of the subregions of the posteromedial cortex (PMC) affected by AD (Xia et al, 2014;Wu et al, 2016;Khan et al, 2020). Among them, Wu et al (2016) reported that disruptions began in a transitional region between the posterior cingulate cortex (PCC) and precuneus, which has an overlap with the V_pcu in this study, in mild AD patients and then spread to other subregions of PMC as the disease became more severe.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…To the best of our knowledge, disrupted FCS within V_pcu (or any subregions of the precuneus), as a reflection of local intrinsic FC, has not been previously reported. Disrupted global FC between V_pcu and other brain regions has been consistently shown by studies investigating differential functional architecture of the subregions of the posteromedial cortex (PMC) affected by AD (Xia et al, 2014;Wu et al, 2016;Khan et al, 2020). Among them, Wu et al (2016) reported that disruptions began in a transitional region between the posterior cingulate cortex (PCC) and precuneus, which has an overlap with the V_pcu in this study, in mild AD patients and then spread to other subregions of PMC as the disease became more severe.…”
Section: Discussionsupporting
confidence: 69%
“…Abbreviations: FSC, functional connectivity strength; SUVR, standard uptake value ratio; CN, cognitively normal; MCI, mild cognitive impairment; AD, Alzheimer's Disease; V_pcu, ventral precuneus; DP_pcu, dorsal posterior precuneus; DA_pcu, dorsal anterior precuneus; ANOVA, analysis of variance. (Khan et al, 2020). Originated from its cytoarchitecture (Cavanna and Trimble, 2006) and agreed by studies utilizing anatomical (Wang et al, 2019) and functional connectivities (Margulies et al, 2009;Ye et al, 2021) in both humans and macaques, three distinct subregions have been suggested, namely the dorsal-anterior, dorsal-posterior and ventral precuneus.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Seed-based connectivity was investigated either through all voxels and ROI across the brain or within known networks. In 6 studies applying the first approach, 3 studies indicated a negative correlation between global Aβ depositions and connectivity in AD patients and CN participants [32], all CN–, CN+, and MCI subjects [10], and SMC participants [33], among which 1 work also found a positive correlation when conducting the analysis merely in MCI patients [10]. Two other studies indicated a positive association between Aβ deposition and FC [17, 20].…”
Section: Resultsmentioning
confidence: 99%
“…PCC/PCUN, as one of the core regions in the default mode network (DMN), has been widely reported to be associated with a decreased rCBF, disrupted activity, and a destructive brain network in subjects with MCI and subjects with AD (Yoshiura et al, 2009 ; Sierra-Marcos, 2017 ; Xue et al, 2019 ). Notably, functional abnormalities of PCC/PCUN were also associated with the increased amyloid burden and decreased hippocampal volume (Khan et al, 2020 ). Additionally, a recent study, which explored the correlation between an altered rCBF and brain function in AD, revealed that the combination of ASL and the amplitude of low-frequency fluctuations (ALFF) in the PCC/PCUN could be used as a potential biomarker for the diagnosis of AD (Zheng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%